(untitled) (Acta Polytechnica CTU Proceedings, 2022)
It has become increasingly clear, that the recent consumption of mineral resources is unsustainable. The Czech Republic produces more than 217,000 tones of mineral wool annually, while its recycling stays unacceptably limited. This paper presents new possibilities how to recycle mineral wool from building insulation systems. Cladding of 30 years old building composed of FOS 125 facade was disassembled and its mineral wool boards were subjected to micro-milling in order to get filler and shortly chopped fibers to be the multifunction micro-aggregate in new design of plaster mortars. It was shown that mortars containing up to 1.2 wt. % of such waste exhibited decrease in pressure strength in the order of tens of percent than those made from reference mixture. On the other side, their bending strength was decreased slightly or oven improved. Other improvement was detected in thermal conductivity.